The Origins of American Industrial Success, 1879-1940 - Wright, Gavin (American Economic Review, 1990)
The United States became the world's preeminent manufacturing nation at the turn of the twentieth century. This study considers the bases for this success by examining the factor content of trade in manufactured goods. Surprisingly, the most distinctive characteristic of U.S. manufacturing exports was intensity in nonreproducible natural resources; furthermore, this relative intensity was increasing between 1880 and 1920. The study then asks whether resource abundance reflected geological endowment or greater exploitation of geological potential. It was mainly the latter.